Seminar and Beauty Class: “Care about Beauty, Care about Health” Health and Beauty Education for Muslim Women - Fitri Anisa Kusumastuti; Muh. Khaedir Lutfi; Nadya Amalia Juana; Fitri Rizkiyah; Sonya Trikandi; Rizqi Nur Rachmawati; Mona Anju Sansena; Dwi Nova Holisiah (Journal of Innovation and Community Engagement, 2025)
Health and beauty are essential aspects of a Muslimah’s life, which Islamic values should maintain as a form of gratitude and responsibility for the body entrusted by Allah. However, a lack of education regarding proper, healthy, and halal self-care practices remains an issue. This community service program aims to enhance Muslim women's understanding of healthy and Islamic-compliant skincare through a seminar and beauty class themed "Care about Beauty, Care about Health". The activities consisted of an educational seminar on skincare awareness and a hands-on beauty class using halal-certified products. The implementation methods included lectures, demonstrations, interactive Q&A sessions, and evaluation via questionnaires. The program involved both academics and halal beauty practitioners from Wardah. The results showed a significant increase in participants' knowledge of skincare techniques and awareness in selecting safe, halal beauty products. Program outputs included an educational self-care module, an article publication, and visual documentation, serving as a reference and evaluation material for future programs. This initiative is expected to have a lasting impact on raising awareness among Muslim women about the importance of maintaining a balanced approach to personal care, one that combines physical wellness with spiritual integrity.